Precise CCM1 gene correction and inactivation in patient‐derived endothelial cells: Modeling Knudson's two‐hit hypothesis in vitro. Issue 7 (23rd May 2019) - Spiegler, Stefanie; Rath, Matthias; Much, Christiane D.; Sendtner, Barbara S.; Felbor, Ute
Abstract: Background: The CRISPR/Cas9 system has opened new perspectives to study the molecular basis of cerebral cavernous malformations (CCMs) in personalized disease models. However, precise genome editing in endothelial and other hard‐to‐transfect cells remains challenging. Methods: In a proof‐of‐principle study, we first isolated blood outgrowth endothelial cells (BOECs) from a CCM1 mutation carrier with multiple CCMs. In a CRISPR/Cas9 gene correction approach, a high‐fidelity Cas9 variant was then transfected into patient‐derived BOECs using a ribonucleoprotein complex and a single‐strand DNA oligonucleotide. In addition, patient‐specific CCM1 knockout clones were expanded after CRISPR/Cas9 gene inactivation. Results: Deep sequencing demonstrated correction of the mutant allele in nearly 33% of all cells whereas no CRISPR/Cas9‐induced mutations in predicted off‐target loci were identified. Corrected BOECs could be cultured in cell mixtures but demonstrated impaired clonal survival. In contrast, CCM1 ‐deficient BOECs displayed increased resistance to stress‐induced apoptotic cell death and could be clonally expanded to high passages. When cultured together, CCM1 ‐deficient BOECs largely replaced corrected as well as heterozygous BOECs. Conclusion: We here demonstrate that a non‐viral CRISPR/Cas9 approach can not only be used for gene knockout but also for precise gene correction in hard‐to‐transfect endothelial cells (ECs). Comparing patient‐derived isogenic CCM1 +/+, CCM1 +/−, and CCM1 −/− ECs, we show that the inactivation of the second allele results in clonal evolution of ECs lacking CCM1 which likely reflects the initiation phase of CCM genesis. Abstract : We here demonstrate that a non‐viral CRISPR/Cas9 approach can not only be used for gene knockout but also for precise gene correction in hard‐to‐transfect endothelial cells. Comparing patient‐derived isogenic CCM1 +/+, CCM1 +/ −, and CCM1 − / − endothelial cells, we show that the inactivation of the second allele results in clonal evolution of endothelial cells lacking CCM1 which likely reflects the initiation phase of CCM genesis.